Analisis Model Pembelajaran Number Head Together Dalam Meningkatkan Keaktifan Siswa - Puji Astutik; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to describe the Joint Head Number Learning model in increasing student activity. This research is a descriptive qualitative study. The research subjects were students of class X OTKP at SMKN 1 Lamongan in general administration subjects, specifically the basic competency of checking documents or incoming and outgoing letters. Data collection techniques using observation, and interviews. With data analysis techniques through data collecttion, data presentation and conclusion. in fact during the learning process students tend to contextual subject matter, so we need an appropriate learning model. The Number Head Together (NHT) learning model is a learning model applied by teachers to create patterns of interaction through mastery and understanding of mater. Through group discussion with numbering in each member, this refutes to discuss students to discuss actively for the learning process to achieve predetermined learning goals. Based on the research it can be concluded as an effective Number Head Together (NHT) learning model. Furthermore, further research can be made up of research to obtain relevant data in the field.